2001
DOI: 10.1523/jneurosci.21-16-06430.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Slow Oscillatory Activity Is Reflected in the Membrane Potential and Spike Trains of Striatal Neurons in Rats with Chronic Nigrostriatal Lesions

Abstract: Neurons in the basal ganglia output nuclei display rhythmic burst firing after chronic nigrostriatal lesions. The thalamocortical network is a strong endogenous generator of oscillatory activity, and the striatum receives a massive projection from the cerebral cortex. Actually, the membrane potential of striatal projection neurons displays periodic shifts between a very negative resting potential (down state) and depolarizing plateaus (up states) during which they can fire action potentials. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
242
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(286 citation statements)
references
References 57 publications
39
242
4
1
Order By: Relevance
“…Striatal firing rate in the lesioned hemisphere was 2.4 times greater than in intact rats (Table 1). These observations are consistent with intracellular recording studies (Tseng et al, 2001b) that demonstrated striatal neurons have more depolarized membrane potentials during both the down-states and up-states and fire more spikes per up-state after dopamine cell lesion.Striatal spike-SNpr LFP phase relationships-When striatal activity was recorded in the lesioned hemisphere in conjunction with SNpr LFP recordings ( Fig. 3C; n=6), spectral analysis of striatal firing rate slow oscillations showed peak frequencies (mean main peak: 1.0 ± 0.2 Hz) similar to peak frequencies of SNpr LFP oscillations (mean main peak: 1.0 ± 0.2 Hz).…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Striatal firing rate in the lesioned hemisphere was 2.4 times greater than in intact rats (Table 1). These observations are consistent with intracellular recording studies (Tseng et al, 2001b) that demonstrated striatal neurons have more depolarized membrane potentials during both the down-states and up-states and fire more spikes per up-state after dopamine cell lesion.Striatal spike-SNpr LFP phase relationships-When striatal activity was recorded in the lesioned hemisphere in conjunction with SNpr LFP recordings ( Fig. 3C; n=6), spectral analysis of striatal firing rate slow oscillations showed peak frequencies (mean main peak: 1.0 ± 0.2 Hz) similar to peak frequencies of SNpr LFP oscillations (mean main peak: 1.0 ± 0.2 Hz).…”
supporting
confidence: 92%
“…In one commonly used animal model of PD, the anesthetized rodent with a unilateral 6-hydroxydopamine (6-OHDA)-induced medial forebrain bundle lesion, a number of studies have found that firing patterns in STN and SNpr become more bursty (Sanderson et al, 1986;MacLeod et al, 1990;Hollerman and Grace, 1992;Burbaud et al, 1995;Hassani et al, 1996;Murer et al, 1997;Rohlfs et al, 1997;Tseng et al, 2000Tseng et al, , 2001aVila et al, 2000;Magill et al, 2001;Ni et al, 2001;Belluscio et al, 2003;Tai et al, 2003). This bursty activity has been shown to be correlated with slow oscillations in cortical EEG (Magill et al, 2001;Tseng et al, 2001b;Belluscio et al, 2003). While one must be cautious about generalizing from results obtained in anesthetized preparations, these preparations have a property that is useful for probing changes in network function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, the effects of dopamine on striatal transmission play a central role in all models of basal ganglia function and in the proposed pathophysiologic mechanisms in both PD and dystonia. Dopamine is released in the striatum and other nodes of the motor circuit from terminals of projections from the substantia nigra pars compacta, and regulates the activity of the basal ganglia output neurons by facilitating corticostriatal transmission upon MSNs of the direct pathway and inhibiting corticostriatal transmission upon MSNs of the indirect pathway ( [99][100][101][102]; Fig. 1).…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 99%